Guidelines for Innovative Leadership Development of Private School Administrators in Kalasin Province - Soonthornchai, Nichapha; Preuksatewed, Asst. Dr. Chawengsak; Chusorn, Dr. Prayuth (Journal for Developing the Social and Community, 2018)
This research were aimed (1) to study the current condition, desired condition and needs developing innovative leadership of private school administrator in Kalasin province, and (2) to study guidelines for developing innovative leadership of private school administrator in Kalasin province. Population were 1,069 people. Sample was the informants consisted of 278 people which were administrators and teachers. Research instrument was questionnaire using dual-response format with modified priority need index (PNI Modified) to prioritize needs. Focus group discussion for finding of guideline innovative leadership of private school administrator in Kalasin province. Target group was 5 experts. Data was analyzed through content analysis and presented in essay format. The finding revealed actual condition and desired condition of innovative leadership of private school administrator in Kalasin province. The current condition indicated highest level was transformational leadership followed by the Innovative Risk- taking. The needs could be ranked based on PNI modified as follows : (1) Visionary innovation, (2) Creative Thinking Innovation, (3) Innovative Strategy, (4) Innovative Risk- taking, and (5) Transformational leadership. The followings are guidelines for developing innovative leadership of private school administrator in Kalasin province. School administrator should have meeting planning for teachers to understand the clear picture. Teacher are involved meeting and planning to get the potential job. Use innovation and technology to work faster and more efficiently.